A Self Psychological Therapy Tool Based on Psychodrama Methodology. Issue 1 (1st January 2018) - Suto, Hidetsugu; Maeda, Jun
Abstract : In the last decade, diversification of communication systems is increasing with the information technology development, and our human relationships are getting more and more complex. Sometimes, we need helps to overcome a difficult situation that we must face in such complicated relationships. Psychodrama is one of the effective counseling methods which are used for finding hints to solve human relationship problems. Despite many advantages of psychodrama have been reported, some weak points also have been pointed out. The first one is that, before conducting a psychodrama event, the participants have to adjust their schedules. The second one is that, some participants may hesitate to talk their problems of human relationships in a public space. These factors make it difficult to conduct psychodrama events easily and comfortably. In this paper, a self psychological therapy tool is proposed as an approach for the problems. The proposed tool aims to provide similar effects with creating social network diagram, which is a basic technique of psychodrama. Experiments have been conducted in order to evaluate the proposed tool. The results show that the proposed tool can provide some hints for the users who had troubles in current human relationships and want to change the situations.